Indo-Russian Strategic Partnership and Indian Military's Cold Start Doctrine - Summar Iqbal Babar; Masood Ur Rehman Khattak; Mujahid Hussain Sargana (Policy Perspectives, 2018)
The South Asian strategic stability is at risk because of the Indian military's doctrinal shift, massive military modernization and operationalization of the Cold Start Doctrine-(CSD) against a nuclear weapon state, Pakistan. This study is divided in two parts. The first part would emphasize on the strategic stability of South Asia and the Indian military's efforts to execute Cold Start Doctrine against Pakistan. Second part would highlight the Indo-Russian defense collaboration and its likely impact on regional security. The Russian T-90 MBTs, SU-30 MKI Air aircraft along with S-400 Air defense system, surveillance and reconnaissance capabilities would be the backbone of any aggressive action against Pakistan. In addition, the Russian assistance in the nuclear submarines would provide India with assured second-strike capability and confidence to go for any misadventure against Pakistan under CSD. The Russian weapon and equipment would revamp the Indian military's overall warfighting capabilities, fill the operational gaps and enable India to operationalize the CSD against Pakistan. Limited war envisaged by the Indian military may not remain limited for Pakistan. Pakistan's quid pro quo response may push India to escalate the conflict which may endanger the deterrence stability in south Asia. Therefore, the Indian CSD is a threat to the regional peace and stability. India needs to consider shunning such types of strategies and resort to peaceful negotiations with Pakistan to resolve all outstanding issues for long term peace and stability in south Asia.